Joint Transcriptomic and Metabolomic Analysis Reveals Differential Flavonoid Biosynthesis in a High-Flavonoid Strawberry Mutant - Lin, Yuanxiu; Hou, Guoyan; Jiang, Yuyan; Liu, Xiaoyang; Yang, Min; Wang, Liangxin; Long, Yu; Li, Mengyao; Zhang, Yunting; Wang, Yan; Chen, Qing; Zhang, Yong; et al. (Frontiers in Plant Science, 2022)
The enriched phenolic content attributes to the promising health benefit of strawberry fruits. On the behalf of screening and seeking the breeding material with high phytochemical composition, a mutant (MT) of strawberry ‘Benihoppe’ (WT) with high total flavonoid content (TFC), especially anthocyanins and proanthocyanidins (PAs), was identified in this study. To investigate the possible reason for these disparities during strawberry fruit development, an integrated transcriptomic and metabolomic analysis was conducted using these two specific materials. As a result, a total of 113 flavonoid compounds were detected, a specific anthocyanin namely petunidin 3-O-rutinoside was detected for the first time in strawberry. By comparing with the WT fruits, a significant reduction of petunidin 3-O-rutinoside while around 24 times higher of cyanidin 3-O-rutinoside in MT fruits were observed. However, the cyanidin 3-glucoside content did not show obvious changes between MT and WT fruits, the pelargonidin and its derivatives were up-regulated only in partial red (PR) stage, not in large green (LG) and fully red (FR) stages. Notably, the PAs such as procyanidin B2, procyanidin A1, catechin, gallocatechin gallate, epigallacatechin and theaflavin were markedly up-regulated in MT. These results revealed a differential flavonoid biosynthesis between the two detected strawberry genotypes. A joint analysis with transcriptome data explained the up-regulation of cyanidin-based anthocyanins and PAs were caused by the down-regulation of F3’5’H, and up-regulation of F3’H and LAR expression, which might be regulated by the upregulation of potential TFs such as C3H, MADS, and AP2/ERF TFs. Metabolite correlation analysis suggested that it was PAs but not anthocyanins strongly correlated with the total phenolic content (TPC), indicated that PAs might contribute more to TPC than anthocyanins in our detected strawberry samples. This study not only potentially provided a new mutant for further breeding program to obtain high flavonoid content strawberry, but also gave insights into strawberry flavonoid metabolic regulatory network, laid the foundation for identifying new flavonoid regulators in strawberry.